The Influence of Human Resource Quality, Human Relations, Work Environment, and Work Facilities on Employee Performance with Motivation as an Intervening Variable - Qudratul Nurjanah, Agustin; Bayu, Muhammad; Dhanny, Omar (Manajemen Bisnis, 2026)
This study aims to analyze the influence of human resource quality, human relations, work environment, and work facilities on employee performance, with work motivation as an intervening variable at PT. Mitra Sukses Raharja. The research employed a quantitative approach using a survey method, and the data were analyzed using Structural Equation Modelling (SEM) to examine the relationships among variables. The results show that the quality of human resources has a positive and significant effect on work motivation and indirectly affects performance through motivation. In contrast, human relations, work environment, and work facilities do not have significant effects on either motivation or performance, whether directly or indirectly. Work motivation was found to have a positive and significant influence on employee performance. These findings indicate that improving human resource quality and strengthening work motivation are key factors in enhancing employee performance. Meanwhile, the management approach to human relations, work environment, and facilities needs to be re-evaluated, as they have yet to demonstrate a measurable impact on employee motivation and performance.